Penilaian Kualitas Pelayanan Jalan Simpang Gajayana-Joyoagung Kota Malang Berdasarkan Pedoman Geometrik Jalan 2021 dan MKJI 1997 - Nain Dhaniarti Raharjo (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
As one of the supporting cities that connects to Batu City, Malang City has several connecting roads that can be alternative to Batu City, which is the Simpang Gajayana road - Joyoagung road, with the function as a secondary collector. Along with the rapid rate of mobility and community growth, many social areas have been developed along this road, so that along this road section becomes crowded with the heavy traffic, and it certainly has an impact on the level of road service. The purpose of this study to determine the value of road service quality along the Simpang Gajayana to Joyoagung road. Assessment carried out is regarding traffic conditions, side barriers, and the geometric condition of the road section, which is based on the 2021 Highway Geometric Guidelines and 1997 Indonesian Highway Capacity Manual. Result of the research shows that the total value of the degree of saturation (DS) on the Simpang Gajayana-Joyo Utomo road is 1,189 and the Joyoutomo-Joyoagung road is 0,61.Â  So, it means that along the Simpang Gajayana-Joyo Utomo road, the quality of services is in category F value (poor condition), because the value of the degree of saturation is above 1 (DS>1). However, the Joyo Utomo-Joyoagung road, the quality of services is in category C value (moderate condition), because the value of degree saturation is below 1 (DS<1). Result from this study can be used as a consideration and reference for related parties in structuring the function of the road network in that area.